Knowledge and appreciation of seeds in Quebrada Seca, Coquimbo region, Chile - Jaime Muñoz, Eduardo (2025)
The study aimed to analyze the knowledge and appreciation of traditional seeds used for the subsistence of farmers in Quebrada Seca, Monte Patria commune, Coquimbo region (Chile). A case study design with a mixed approach was applied, using qualitative techniques (semi-structured interviews and photographic records) and quantitative techniques (record of agricultural varieties). A geographic map of the area was created using satellite images obtained from Google Earth (2024). The results show the existence of 40 seed varieties cultivated through different agricultural techniques transmitted by oral tradition. The study concludes that these seeds constitute an agricultural and cultural heritage at risk of disappearing, whose preservation requires sustainable community actions.